EVALUASI PROGRAM SIARAN PENDIDIKAN INTERAKTIF TELEVISI EDUKASI MATA PELAJARAN IPA - Susanti Murwitaningsih (Jurnal Evaluasi Pendidikan, 2016)
The purpose of this study is to explain the effectiveness of the interactive Education Broadcast Programs for Science Subject. The program is broadcasted by Pustekkom on its Televisi Edukasi channel a head of the National Exam. The study uses the Countenance evaluation model developed by Stake. The study founds that 89,47% of the antecedent and 84,61% of the transactions aspects of the program meet the evaluation standard, while only 66,67% of the outcome aspects do. The results show that even though the program has met most of the standard for the antecedent and transactions aspects, it does not necessarily yield good outcomes. While this program has a good preparation and implementation, it is yet to provide an optimum benefit for students. An analysis of this study concludes that while the program is in line with the on going curriculum, and despite students’ high interest, it is yet to accommodate students’ needs or give maximum contribution due to lack of promotion and access to broadcasting schedule with some colliding with students’ study time. I recommend maintaining the program and making improvements: providing reruns, increasing the broadcast frequency by broadcasting on national TV channels, Facebook fun page, TVE’s website or by distributing booklets. I also recommend replacing or training mentors so that they master the subject they teach. I recommend that the program refrain from using very formal or stiff language.